Analisa Kebutuhan Air Bersih pada RSUD Kabupaten Ogan Ilir : Analysis of Clean Water Needs at Ogan Ilir District Hospital - Adhe Yundri Tunggal Prasetio (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
This study aims to analyze the clean water needs at the Regional General Hospital (RSUD) of Ogan Ilir Regency. The analysis includes calculations of clean water requirements for staff and patients, as well as the water discharge supplied from bore wells to the reservoir. The results indicate that the hospital's average daily clean water demand is 102,120 liters (102.12 m³), with a maximum daily requirement of 127,650 liters (127.65 m³). However, the available supply is only 35,250 liters (35.25 m³), leading to a significant deficit in meeting the demand. Additionally, the water quality from bore wells does not meet the standards for clean water. This study recommends improved planning and management of reservoirs, increasing water storage capacity, and evaluating the piping system and water pressure to ensure optimal distribution. Implementing these solutions is expected to ensure the sustainability of the clean water supply, thereby supporting optimal healthcare services.